2017
DOI: 10.1111/ejh.12876
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of relapsed or refractory multiple myeloma: Results from an international trial

Abstract: Substantial RRMM indirect, social costs were observed. Better major tumor response may reduce hospital visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Real-world considerations such as the tolerability, convenience, and practicality of therapy are not captured within clinical trial reports or using conventional endpoints; however, they may also contribute to discrepancies between clinical trial and real-world outcomes. For example, treatment with a novel agent or regimen in the real-world setting may be associated with substantial patient time and economic burden 91 , 92 , including direct and indirect costs associated with medications and attending regular clinic visits. The burden of treatment, such as the route of administration and travel to the treatment center 10 , 93 , may not be captured by standard clinical trial endpoints but may substantially affect the feasibility of long-term treatment in the real-world setting as patients may succumb to treatment fatigue outside of the ‘motivating’ environment of clinical trial participation.…”
Section: Understanding Disparities Between Different Clinical Trials mentioning
confidence: 99%
“…Real-world considerations such as the tolerability, convenience, and practicality of therapy are not captured within clinical trial reports or using conventional endpoints; however, they may also contribute to discrepancies between clinical trial and real-world outcomes. For example, treatment with a novel agent or regimen in the real-world setting may be associated with substantial patient time and economic burden 91 , 92 , including direct and indirect costs associated with medications and attending regular clinic visits. The burden of treatment, such as the route of administration and travel to the treatment center 10 , 93 , may not be captured by standard clinical trial endpoints but may substantially affect the feasibility of long-term treatment in the real-world setting as patients may succumb to treatment fatigue outside of the ‘motivating’ environment of clinical trial participation.…”
Section: Understanding Disparities Between Different Clinical Trials mentioning
confidence: 99%
“…MM is also related to increased healthcare utilisation and high healthcare costs [5,6]. A recent study found that 42% of MM patients reported at least one disease-driven hospital visit during the previous six months, 71% declared at least one specialty visit during the three months prior, and 9% received emergency care in the previous three months [6].…”
Section: Introductionmentioning
confidence: 99%
“…MM is also related to increased healthcare utilisation and high healthcare costs [5,6]. A recent study found that 42% of MM patients reported at least one disease-driven hospital visit during the previous six months, 71% declared at least one specialty visit during the three months prior, and 9% received emergency care in the previous three months [6]. Healthcare costs per MM patient have increased steadily between 2000 and 2014 for all healthcare services including treatment-related drug costs, the main contributor being outpatient visits [7].…”
Section: Introductionmentioning
confidence: 99%
“…Específicamente, el 94,4% del coste total se asocia a costes directos derivados de servicios ambulatorios (49,1%), hospitalizaciones (32,7%) y prescripciones complementarias (18,2%) 28 . Dicha estimación se llevó a cabo en base a las tendencias en supervivencia y costes asociados al MM en Estados Unidos 9,29 . En consecuencia, estos resultados deben contemplarse con precaución por la dificultad de extrapolar dicha tendencia a otros países con sistemas sanitarios diferentes.…”
Section: Carga Económicaunclassified